Capability needs and management performance of Punong Barangays in Iloilo City - Apresto, Heireyne Joy D.; Boniba, Juvelyn C.; Daynolo, Shella Marie B.; Quisoy, Sheila E.; Samillano, Cheril A.
The study was conducted to find out whether capability needs affect management performance of Punong Barangays in Iloilo City. The study specifically aims to: 1) describe the socio-demographic and economic profile of Punong Barangays ; 2) find out if Punong Barangays have capabilities in participatory decision-making and administrative communication ; 3) identify the capability needs of Punong Batngays in terms of participatory decision-making and administrative communication ; 4) determine the management performance of Punong Barangays in terms of development planning and fiscal management ; 5) recommend measures to improve the management performance of Punong Barangays. The study is descriptive and analytical in nature. A total of 60 Punong Barangays were randomly selected as respondents. The survey method was used in gathering data. Data gathered was subject to description and analysis such as frequencies and chi-square test. The results show that, capability needs affect management performance of Punong Barangays. The higher the capability need, the lower is the performance and the lower the capability need, the higher is the performance. Results also revealed that the socio-demographic and economic profile of the Punong Barangays do not affect their management performance.